Aqueous Batteries: Dual Anion–Cation Reversible Insertion in a Bipyridinium–Diamide Triad as the Negative Electrode for Aqueous Batteries (Adv. Energy Mater. 8/2018). Issue 8 (15th March 2018) - Perticarari, Sofia; Sayed‐Ahmad‐Baraza, Yuman; Ewels, Chris; Moreau, Philippe; Guyomard, Dominique; Poizot, Philippe; Odobel, Fabrice; Gaubicher, Joël
Abstract : In article number1701988, Joël Gaubicher, Philippe Poizot, Fabrice Odobel and co‐workers report the first ever battery material that works with simultaneous uptake and release of both cations and anions. This represents one of a new family of organic electrode materials that shows great promise, thereby promoting the design of cutting‐edge, low‐cost, rocking‐chair dual‐ion aqueous batteries.